2017
DOI: 10.1152/ajpendo.00146.2017
|View full text |Cite
|
Sign up to set email alerts
|

Circulating soluble RAGE isoforms are attenuated in obese, impaired-glucose-tolerant individuals and are associated with the development of type 2 diabetes

Abstract: The soluble receptor for advanced glycation end products (sRAGE) may be protective against inflammation associated with obesity and type 2 diabetes (T2DM). The aim of this study was to determine the distribution of sRAGE isoforms and whether sRAGE isoforms are associated with risk of T2DM development in subjects spanning the glucose tolerance continuum. In this retrospective analysis, circulating total sRAGE and endogenous secretory RAGE (esRAGE) were quantified via ELISA, and cleaved RAGE (cRAGE) was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 59 publications
3
57
1
2
Order By: Relevance
“…The above factors were selected for investigation due to their independent importance in disease pathophysiology and sRAGE biology. For example, we have previously found that glucose tolerance and obesity have a strong influence on sRAGE [ 29 ] and that adiposity (fat mass) is associated with attenuated sRAGE pools [ 35 ]. Further, this project aimed to characterize sRAGE profiles by cognitive status and commonly used markers of metabolic health to serve as a foundation for future work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The above factors were selected for investigation due to their independent importance in disease pathophysiology and sRAGE biology. For example, we have previously found that glucose tolerance and obesity have a strong influence on sRAGE [ 29 ] and that adiposity (fat mass) is associated with attenuated sRAGE pools [ 35 ]. Further, this project aimed to characterize sRAGE profiles by cognitive status and commonly used markers of metabolic health to serve as a foundation for future work.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin (Genway), amylin (Millipore), S100B (Millipore), sRAGE (R&D), and esRAGE (As One International) were quantified using ELISA per the manufacturer's protocol. Serum cRAGE was computed by subtracting esRAGE from the total plasma sRAGE pool as previously described [ 33 ], and the cRAGE : esRAGE ratio was subsequently calculated [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that esRAGE has the strongest correlation with BMI and body fat percentage, where changes in esRAGE negatively correlate with fat mass changes . Conversely, a significant increase in total sRAGE as a result of weight‐loss 24 and 36 months after bariatric surgery was verified .…”
Section: Discussionmentioning
confidence: 74%
“…Thus, future mechanistic work is necessary to determine if changes in adiponectin secretion and the proportion of circulating sRAGE isoforms are in fact causally linked . Although not many studies have investigated the sRAGE isoforms changes after weight loss, it was shown that improvements in body composition are related to increased sRAGE isoforms …”
Section: Discussionmentioning
confidence: 99%